2016
DOI: 10.1177/2055217316680639
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of exercise interventions to improve sleep quality and daytime sleepiness in individuals with multiple sclerosis: A pilot study

Abstract: BackgroundNearly 70% of individuals with multiple sclerosis (MS) experience sleep disturbances. Increasing physical activity in people with MS has been shown to produce a moderate improvement in sleep quality, and exercise has been shown to improve sleep quality in non-neurologically impaired adults.ObjectiveThe purpose of this pilot randomized controlled trial study was to examine the effect of two exercise interventions on sleep quality and daytime sleepiness in individuals with MS.MethodsTwenty-eight indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…Our results are consistent with other studies in different populations; in a population of women with multiple sclerosis, Siengsukon et al 23 showed a moderate improvement in sleep quality after a low-intensity walking and stretching programme. Tworoger et al 24 and D'Aurea et al 25 also showed improvement in their sleep quality after stretching in postmenopausal women and chronic insomnia patients.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with other studies in different populations; in a population of women with multiple sclerosis, Siengsukon et al 23 showed a moderate improvement in sleep quality after a low-intensity walking and stretching programme. Tworoger et al 24 and D'Aurea et al 25 also showed improvement in their sleep quality after stretching in postmenopausal women and chronic insomnia patients.…”
Section: Discussionsupporting
confidence: 93%
“…Our second hypothesis, following Siengsukon et al (56), was that a 3-week program of regular exercise would improve subjective sleep, and this was confirmed. These findings therefore replicate those from the only previous study of which we are aware, that by Siengsukon et al (56). However, we expanded upon their study, in finding significant changes in subjective sleep within a 3-week period.…”
Section: Discussionsupporting
confidence: 54%
“…However, there are only a few studies on the benefits of interventions for MS patients. As one example, Siengsukon et al (56) randomly allocated 28 MS patients either to moderate-intensive aerobic exercise or to low-intensive walking/stretching. Patients engaged in one or other of these activities for 30 min three times a week, and for consecutive 12 weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations hold also true as regards the associations between sleep patterns and physical activity behaviors. For non-clinical samples ( 19 28 ), clinical samples ( 29 , 30 ), and samples with PwMS ( 31 36 ), favorable sleep indices were associated with higher physical activity indices. Despite this, longitudinal studies on the development of sleep and physical activity indices over time are scarce.…”
Section: Introductionmentioning
confidence: 96%